The role of archaisms in the Latin inscriptions of the Roman Empire: some new considerations in light of computerized dialectology - Tantimonaco, Silvia (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper aims to reconsider the role of archaisms in epigraphy and, above all, their possible dialectal value. Indeed, according to a traditional theory, provinces that were colonized earlier by the Romans preserved archaic varieties of Latin. Scholars have often used inscriptions to support this idea, particularly in the case of Hispania, but the results of this paper, which rely on the methodology of modern Computerized Dialectology, are negative in this regard.